Analisis Perkembangan Standar Pelayanan Fasilitas Di Terminal Bandar Tjilik Riwut Palangkaraya - Alfirani Dwi Putri (Politeknik Kampar, 2023)
Airport quality is very important for consumers who use airport services. Tjilik Riwut Airport serves both pioneer and domestic flights. Terminal Inspection Service is a unit that pays attention to the safety, comfort, smoothness and safety of passengers. The main task of the Terminal Inspection Service is to supervise and observe facilities that support operations. By using qualitative research methods, and supported by data analysis techniques, data reduction, data display, and conclusions in order to obtain valid and objective results. Analysis of the development of facility service standards at the Tjilik Riwut Palangkaraya Airport terminal, one of the facilities at Tjilik Riwut Airport, namely the Lift Facilities which are marked with the reason they cannot be used so that passengers who experience late show up cannot use these facilities to the fullest in certain circumstances. Other facilities that cannot be used are ATM Center facilities, which are decreasing in number, the Terminal Inspection Service is optimizing the development of service users at Tjilik Riwut Airport, Palangkaraya.